The effects of a STEM-based intervention on middle school students' science achievement and learning motivation - Salih Uzun; Nihat Şen (Journal of Pedagogical Research, 2023)
The goal of STEM education is to integrate the disciplines of science, technology, engineering, and mathematics in a way that facilitates holistic learning. Students are also supported in developing creative solutions to problems using the STEM approach. Other STEM fields are often linked through engineering and engineering design. Throughout this study, students participated in engineering design-oriented activities that connected STEM disciplines. This study aims to reveal the effect of a learning environment based on the STEM approach in science education on students' academic achievement and motivation. This study used a quasi-experimental, non-equivalent pretest-posttest control group design. Seventh-graders who attended a public middle school in the Aegean Region of Türkiye participated in the study. The research findings showed a significant difference in science achievement between the control group in the curriculum-based learning environment and the experimental group in the STEM-based learning environment. It was found, however, that motivation toward science was not significantly different. The results indicated that the STEM-based learning environment positively affected science achievement.